Peningkatan Kualitas Bahan Baku Pengrajin Batubata Di Desa Panyyangkalang Kecamatan Bajeng Kabupaten Gowa - Sufriadin .; Irzal Nur; Sri Widodo; Djamaluddin .; Nirmana Fiqra Qaidahiyni; Andi Arumansawang; Asta Arjunoarwan Hatta; Nur Alam Fajar (Faculty of Engineering UNHAS, 2024)
Craftsman group of earth brick at Ballaparang sub village, Panyyangkalang village of Bajeng Subdistrict in the Gowa Regency has long been produced bricks mainly for the construction materials in the Makassar City and Gowa. However, some problems arisen by the craftsman such as brick quality produced is crack easily and the brick maturity during firing is difficult to control. To solve the problem, it was performed the counseling activity with the aims at increasing the brick quality through firing test with controlled temperature and time. The compressive strength test was conducted and compared to the brick produced by craftsman. In addition, mineralogical and chemical testing of raw material was performed using X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) methods respectively. Compressive strength test was carried out for both bricks produced by craftsman and brick fired in laboratory using Unconfined Compressive Strength (UCS) method. Testing results show that clay raw materials were composed of feldspar (plagioclase), quartz, illite, nacrite, and magnetite. Chemical testing exhibits that iron oxides (Fe2O3) is high so it is suggested to reduce the iron content in raw materials by using low-intensity magnetic separator. The implementation results of compressive strength produced by craftsman provide the average value of 3.03 MPa whereas brick fired in the laboratory give the minimum value of 5.09 Mpa which was achieved in 6 hour and 500oC firing. The contribution of this activity indicates the improvement of brick quality mainly compressive strength up to 59 %.